Rachilde et ses «Mercuriales» - Lair, Samuel (Wydawnictwo Naukowe UAM, 2007)
The emblem of decadence, Rachilde's literature is regarded as obscure, meant for the "happy few" who are fond of a modernity which is now outdated. In a field where languidness and the wild lyricism of imagination predominate, the criticisms written by the novel columnist are remarkable for their strength and the efficiency of their approach. For more than thirty years, in the columns of Mercure de France, she used her talent as a reader, applying herself to protecting the review's favourite novelists, praising some novel for their authenticity while denouncing the bad quality of others pieces of work. Her production, which covered a large number of novels, stood out. However, her work is not free of errors. Besides the names that she wants to promote, the article examines the liberties she allows herself to take with literary criticism, however codified this genre might be: recurrence of themes, outline of a poetical approach of the novel, quest for action, longing for a moral dimension, reinstatement of a function of the novel as entertainment. All these elements reveal how she manages to avoid the constraint of the critical exercise, putting her own mark on a practice which is traditionally distant from pure creation. Thus, criticism can function as a laboratory for the art of writing.
Rachilde's Mercuriales
Keywords: Rachilde's literature; Mercuriales